Route of Administration for Highly Orally Bioavailable Antibiotics. (4th October 2017) - Smith, Michael; Shah, Samir; Kronman, Matthew; Patel, Sameer; Thurm, Cary; Hersh, Adam L
Abstract: Background: IDSA guidelines recommend that hospitals implement interventions to switch from intravenous (IV) to oral (PO) routes of administration for antibiotics with high oral bioavailability (HOB). Patterns of use of HOB antibiotics at children's hospitals are unknown. Methods: We used 2015 data from the Pediatric Health Information System (PHIS). Patients were included if they were hospitalized for >48 hours and were eligible for oral conversion as defined by receipt of ≥ 1 non-antibiotic medication by mouth on the same day as a HOB antibiotic (clindamycin, metronidazole, ciprofloxacin, levofloxacin, doxycycline, linezolid or rifampin). Days of therapy (DOT) for each drug were reported overall and stratified by route (IV or PO) and hospital. Costs were estimated by applying institution-specific cost-to-charge ratios. Maximum cost savings were estimated assuming that all doses had been administered orally. Results: 38, 993 children received 221, 535 DOT. Total DOT, route and range of PO use across the 48 PHIS hospitals for each medication are presented in the table. Overall, only 36% of HOB DOT were administered orally. Clindamycin accounted for almost half of all DOT for HOB antibiotics but also had the lowest percentage of PO DOT. The total cost for all medications administered was $11, 831, 139. If all doses had been administered PO the estimated cost would have been $5, 603, 606. Conclusion: There is ample opportunity for implementation of IV to PO switch programs in children's hospitals. Clindamycin should be a priority target for such programs. It represented nearly one-half of all DOTs in this cohort and was more often administered IV. Such programs would be cost saving; we estimated a near 50% decrease in direct drug cost alone. This does not take into account additional potential savings from decreased length of stay or catheter-associated complications. Disclosures: All authors: No reported disclosures.